A comparison of thickness of the serratus anterior muscle during contraction between dominant and non-dominant hands in healthy individuals - Wannaprom, Nipaporn; Khamkruang, Jirawan; Puachaikul, Jakkapop; Uthaikhup, Sureeporn (Journal of Associated Medical Sciences, 2017)
Background: Serratus anterior muscle is an important muscle that helps to increase stability and to control movements of the scapula. Whether there is influence of hand dominance on thickness of the serratus anterior during contraction is unknown. Objectives: To compare thickness of the serratus anterior muscle between the dominant and non-dominant hands during muscle contraction. Materials and methods: Twenty healthy men were recruited for the study. The thickness of the serratus anterior muscle was bilaterally measured in a wall push-up position using ultrasound imaging. Measurement of the serratus anterior thickness was performed three times using Image J software. Results: The serratus anterior thickness on the dominant hand was significantly greater than that on the non-dominant hand (p<0.05). Conclusion: Hand dominance has an influence on the thickness of the serratus anterior muscle during contraction. This should be taken into consideration in future research when determining the serratus anterior muscle.